Growth, Health, and Carcass Traits of Broilers Supplemented with Acalypha australis L. Leaf Extract, Whey Protein, or their Combination in the Diet - Sugiharto, S.; Agusetyaningsih, I.; Widiastuti, E.; Wahyuni, H. I.; Yudiarti, T.; Sartono, T. A. (Tropical Animal Science Journal, 2023)
The study aimed to investigate the effect of dietary administration of Acalypha australis L. leaf extract, whey powder, or a combination of both on the growth, physiological condition, and carcass traits of broilers. A total of 392 broiler chicks was divided into four groups based on a fully randomized design, including (1) control (C, basal feed without additives), (2) basal feed supplemented with 1% Acalypha australis L. leaf extract (AALE), (3) basal feed with 1% whey powder (WHEY), and (4) basal feed with 1% Acalypha australis L. extract and 1% whey powder (AALEWHEY). Samples (i.e., internal organs, blood, intestinal digesta, small intestinal segments, and breast and thigh meats) were collected on day 33. Data were treated with an analysis of variance followed by Duncan’s multiple analysis. Treatments did not affect body weight, feed intake, and feed conversion ratio (p>0.05). Abdominal fat was higher in the treated broilers than in the control (C) (p